ERK and Not p38 Pathway Is Required for IL-12 Restoration of T Cell IL-2 and IFN-γ in a Rodent Model of Alcohol Intoxication and Burn Injury - Li, Xiaoling (2009)
Previous studies from our laboratory have shown that acute alcohol/ethanol (EtOH) intoxication combined with burn injury suppresses T cell IL-2 and IFN-γ production by inhibiting p38 and ERK activation. Because IL-12 plays a major role in Th1 differentiation and IFN-γ production, we examined whether diminished IL-2 and IFN-γ production after EtOH plus burn injury resulted from a decrease in IL-12. Furthermore, we investigated whether IL-12 utilizes the p38/ERK pathway to modulate T cell IL-2 and IFN-γ production after EtOH and burn injury. Male rats (~250 g) were gavaged with 5 ml of 20% EtOH 4 h before ~12.5% total body surface area burn or sham injury. Rats were sacrificed on day 1 after injury, and mesenteric lymph node T cells were isolated. T cells were stimulated with anti-CD3 in the absence or presence of rIL-12 (10 ng/ml) for 5 min and lysed. Lysates were analyzed for p38/ERK protein and phosphorylation levels using specific Abs and Western blot. In some experiments, T cells were cultured for 48 h with or without the inhibitors of p38 (10 μM SB203580/SB202190) or ERK (50 μM PD98059) to delineate the role of p38 and ERK in IL-12-mediated restoration of IL-2 and IFN-γ. Our findings indicate that IL-12 normalizes both p38 and ERK activation in T cells, but the results obtained using p38 and ERK inhibitors indicate that the restoration of ERK plays a predominant role in IL-12-mediated restoration of T cell IL-2 and IFN-γ production after EtOH and burn injury.